2014
DOI: 10.1002/cctc.201301015
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Zinc–N‐Heterocyclic Carbene Complexes for Either the Controlled Ring‐Opening Polymerization of Lactide or the Controlled Degradation of Polylactide Under Mild Conditions

Abstract: We describe the synthesis of the new Zn–N‐heterocyclic carbene (NHC) alkoxide complexes [(S,CNHC)ZnCl(OBn)]2 (5) and [(O,CNHC)ZnCl(OBn)]2 (6) for use as ring‐opening polymerization (ROP) initiators for lactide polymerization. Complexes 5 and 6 are readily available through an alcoholysis reaction between BnOH and the corresponding Zn–NHC ethyl species [(S,CNHC)ZnCl(Et)] (3) and [(O,CNHC)ZnCl(Et)] (4), and species 3 and 4 were obtained from the reaction of ZnEt2 with the N‐methyl‐N'‐ethylphenylsulfide (1⋅HCl) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 109 publications
3
80
0
Order By: Relevance
“…When rac-lactide is used, no clear preference for (R,R)-lactide vs. (S,S)-lactide insertion was found, therefore atactic polymer formation is predicted. A thorough DFT study of latide ROP initiated by an NHC zinc complex was also reported and showed the assistance of the second metal center [45]. These calculations provided valuable information on the design and development of homogeneous transition and main-group metal polymerization catalysts.…”
Section: Introductionmentioning
confidence: 96%
“…When rac-lactide is used, no clear preference for (R,R)-lactide vs. (S,S)-lactide insertion was found, therefore atactic polymer formation is predicted. A thorough DFT study of latide ROP initiated by an NHC zinc complex was also reported and showed the assistance of the second metal center [45]. These calculations provided valuable information on the design and development of homogeneous transition and main-group metal polymerization catalysts.…”
Section: Introductionmentioning
confidence: 96%
“…Multinuclear metal catalysts, such as yttrium, rare earths, group IV, iron, magnesium, copper, zinc, and aluminum have received enormous attention for ROP of cyclic esters. Tolman and co‐workers reported that the polymerization rate for LA with dinuclear zinc catalysts compares favourably to the fastest catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…The present work had the purpose to elucidate how largely different temperatures and reaction times influence nature and extent of transesterification reactions and, thus, the molecular weight distribution (MWD) of the resulting polylactides. For the sake of completion two recent publications dealing with reaction mechanisms of lactide in the presence of zinc catalysts should be mentioned, but these references are not relevant for the discussion of the present work …”
Section: Introductionmentioning
confidence: 99%